2014
DOI: 10.1016/j.bmcl.2014.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial chemotherapy: Artemisinin-derived dimer carbonates and thiocarbonates

Abstract: Several 2-carbon-linked trioxane dimer secondary alcohol carbonates 14 and thiocarbonates 15, combined with mefloquine and administered in a low single oral dose, prolonged the survival times of malaria-infected mice much more effectively than the popular monomeric antimalarial drug artemether plus mefloquine. Three dimer carbonates 14 and one dimer thiocarbonate 15 partially cured malaria-infected mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Connecting these precursors chemically with one or more other natural product fragments lead to the formation of hybrid compounds. [19][20][21][22][23][24][25][26][27][28][29][30] These hybrids often possess strikingly improved or new biological activities compared to their parent compounds. Although none of these hybrids have reached clinical application yet, there are many examples available in literature with already very promising in vivo results demonstrating the great potential of the hybridization concept.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Connecting these precursors chemically with one or more other natural product fragments lead to the formation of hybrid compounds. [19][20][21][22][23][24][25][26][27][28][29][30] These hybrids often possess strikingly improved or new biological activities compared to their parent compounds. Although none of these hybrids have reached clinical application yet, there are many examples available in literature with already very promising in vivo results demonstrating the great potential of the hybridization concept.…”
Section: Introductionmentioning
confidence: 99%
“…Although none of these hybrids have reached clinical application yet, there are many examples available in literature with already very promising in vivo results demonstrating the great potential of the hybridization concept. [28,29,[31][32][33][34][35][36] In this study, four artemisinin-derived hybrids 4-7 ( Figure 2) were synthesized and investigated for their potency against the malaria parasites P. falciparum 3D7 strain, the leukemia cell lines CCRF-CEM and CEM/ADR5000 as well as against HCMV. Dimer 4 is known from literature, [37] but was prepared only by degradation of artesunic acid (3) and up to now not investigated for its potential against cancer cells and HCMV.…”
Section: Introductionmentioning
confidence: 99%
“…Oxime formation of alcohol dimer 15c with hydroxylamine and NaOAc in refluxing CH 2 Cl 2 gave trioxane dimer 108a. 98 As mentioned before, Moon et al 99 116a-e, carbonates 114a-o and alcohols/carbamates 115a-n, investigated by Posner et al for their in vivo antimalarial potential, 83,88,101 were accessible from artemisinin derived ketone 64 (Scheme 14). To convert ketone 64 into oximes 112a-f, pyridine and the corresponding hydroxylamine were applied.…”
Section: Anticancer Activitymentioning
confidence: 97%
“…Among them, five dimers 5a,b and 6a‐c displayed higher in vivo efficiency as they could prolong the life of infected mice (25‐30 d), compared with the combination use of artemether and mefloquine hydrochloride (20.3 d) or mefloquine hydrochloride alone (20.3 d). Further study revealed that introduction of carbonate, thiocarbonate ( 8 ) or ketone, and oxime ( 9 ) into two‐carbon linker could also maintain the activity, and dimers with thiocarbonate (X═S) or oxime exhibited higher activity than the corresponding carbonate or ketone analogs (X═O) . For dimers 8 , alkyl at R position gave better activity than aromatic ring did, and branched alkyl was more favorable than linear alkyl in terms of activity.…”
Section: Alkyl‐tethered Artemisinin‐derived Dimersmentioning
confidence: 99%